PENGARUH GAYA KEPEMIMPINAN BERORIENTASI PADA TUGAS DAN BERORIENTASI PADA HUBUNGAN TERHADAP KINERJA KARYAWAN STIKES DAN AKBID dr. SOEBANDI JEMBER - Faridha Puspitasari; Irwin Santoni (Jurnal Kesehatan dr. Soebandi, 2017)
The attraction and importance to determine a form of how to influence subordinates and their perception of the leader is a central rhythm that is very necessary to get attention in the study of leadership. This study was intended to determine the effect of leadership style on the performance of Stikes and Akbid employees from Soebandi Jember. In this study the number of samples were 97 employees of Stikes and Akbid Dr. Soebandi Jember with the sampling method being saturated. The analytical model used in this study is Multiple Linear Regression. Statistical test results on the significance of the regression coefficients simultaneously or partially have a positive effect. As for the effects together, there is an effect of 75.50%, while the remaining 24.50% is influenced by other variables not included in this model. so the first hypothesis is accepted. Partial influence, all independent variables (task-oriented leadership, and relationship-oriented leadership) influence the dependent variable (the performance of Stikes and Akbid employees from Soebandi Jember), so that the second hypothesis is accepted. Among the independent variables that have a dominant influence is the relationship-oriented leadership variable, so the third hypothesis is rejected